Condensation Heat Transfer Efficiency Analysis of Horizontal Double-Sided Enhanced Tubes - Jianghui Zhang; Junjie Wu; He Zhou; Jiaxiang Yu; Bin Zhang; Wei Li; Yan He (Energies)
The enhanced tubes in this study, referred to as E1 and E2, represent significant improvements in the design and performance of smooth tubes. By increasing the surface area on their fin side and optimizing the condensation drainage design, the heat transfer capacity of the finned tubes has been further enhanced. These modifications will provide superior thermal management performance for condenser tubes in practical applications, facilitating their widespread use across various engineering fields. In this experiment, R134a was used as the working fluid, with a test section length (L) of 248 mm for the experimental tubes E1 and E2. The experiments were conducted at a saturation temperature of 40 °C, where the refrigerant condensed outside the tube while deionized water circulated inside. The results indicated that, at a heat flux density below 94 kW/m2, the condensation heat transfer coefficient of the E1 tube was 2–5% higher than that of the E2 tube, achieving values that were 11.63–14.42 times and 10.94–14.67 times that of smooth tubes of identical dimensions and materials, respectively. At a heat flux density of 94 kW/m2, the heat transfer coefficient of E2 exceeded that of E1, with E1 exhibiting a more pronounced decline. Under constant water velocity, the heat transfer coefficient outside the tube initially decreased and then increased as the heat flux density rose. The corresponding effective heat transfer area of E1 increased, leading to better overall heat transfer performance compared to E2.